Computational and experimental study of the orifice discharge coefficient influenced by the presence of a rigid plate. (15th November 2007) - Tang, Clement; Chang, Young
The effect of an impingement plate on the discharge coefficient of a circular hole was investigated. A commercial fluid dynamics package was used, and the computational results were verified experimentally for selected cases. The discharge coefficient was strongly affected by the air gap only when it was small (less than the radius of the orifice). This study can be applied to the flotation of a thin film at the air reverser or other fluid-structure problems, where a coated film or wet paper is supported by air cushion for non-contact support or drying.